2020
DOI: 10.1016/j.heliyon.2020.e03752
|View full text |Cite
|
Sign up to set email alerts
|

The effect of α-terpineol enantiomers on biomarkers of rats fed a high-fat diet

Abstract: Alpha-terpineol is a monoterpenoid found in many essential oils, being widely used in food and household products. In vitro antioxidant and anti-inflammatory activities have already been associated with this alcohol; therefore, this study aimed to check if these properties were also present in vivo, counteracting the oxidant and inflammatory effects of a high-fat diet, as well as if there were differences in the biological activities among the two α-terpineol enantiomers. Thus, this work evaluated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…number 432628) and Fluka's (+)-α-terpineol (≥ 97%, CAS 7785-53-7, Cat. number 83073) with an ee of 16% (for the S-(−)-isomer) and 30% (for the R-(+)-isomer), respectively (Sousa et al 2020). These studies indicate that the potential economically feasible biotechnological processes for the production of α-terpineol are available and also that the enantiospecificity of such a process may be useful to generate enantiomerically enriched products.…”
Section: Biotechnological Productionmentioning
confidence: 75%
“…number 432628) and Fluka's (+)-α-terpineol (≥ 97%, CAS 7785-53-7, Cat. number 83073) with an ee of 16% (for the S-(−)-isomer) and 30% (for the R-(+)-isomer), respectively (Sousa et al 2020). These studies indicate that the potential economically feasible biotechnological processes for the production of α-terpineol are available and also that the enantiospecificity of such a process may be useful to generate enantiomerically enriched products.…”
Section: Biotechnological Productionmentioning
confidence: 75%
“…Although rosmarinic acid (10–200 mg/kg) and allantoin (5 mg/kg) have been reported to possess beneficial effects in mice fed an HFD [ 36 , 43 , 44 , 45 ], the effective concentrations of rosmarinic acid and allantoin administered directly into animals in the aforementioned references appears too high to be reached in vivo by administration of 200 mg/kg M-LB/CS in the present study. In addition, HPLC chromatogram after eluting LBE and CSE indicated that there were many peaks beyond rosmarinic acid and allantoin, and several phytochemicals contained in two herbs (e.g., ursolic acid, oleanolic acid, caffeic acid, luteolin, rutin, maysin, and α-terpineol) also have potential to alleviate obesity [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Therefore, not only rosmarinic acid/allantoin, but also other phytochemicals existing in LBE and CSE may collaboratively contribute to reduce hypertrophy of the fat tissue and resolve abnormal lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…α-Terpineol exhibited anti-hypertension, antiproliferation, anti-inflammation, anti-bacteria and antioxidant. Moreover, it could re-establish insulin sensitivity [ 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%